PENERAPAN PRINSIP DAN PRAKTIK DEMOKRASI INTEGRASI KURIKULUM TERPADU STUDENT CENTERING DI KOTA MEDAN - Safran; Ahmad Tarmizi Hasibuan; Fitri Yuliawati (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2021)
Student-centered curriculum integration or often referred to as Curriculum Integration (CI) is a concept that is supported by democratic education. It places students at the center of learning, involving them in classroom decisions and curriculum planning. This paper examines what happens when three teachers, located in three schools in the city of Medan, explore the democratic principles and practices inherent in the integration of a student-centred curriculum. This study is a small-scale qualitative project, so interpretation of the findings should be viewed with participatory action research (PAR). The data collection technique is triangulation. The findings show that the forms of application of democratic principles and practices of student-centered Curriculum Integration in elementary schools in Medan are democratic thinking-pedagogy and practice, skillful in questioning; build a sense of community through joint decision making, jointly built curriculum.